2018
DOI: 10.1039/c8ra08869a
|View full text |Cite
|
Sign up to set email alerts
|

3D plum candy-like NiCoMnO4@graphene as anodes for high-performance lithium-ion batteries

Abstract: 3D plum candy-like NiCoMnO4 microspheres have been prepared via ultrasonic spraying and subsequently wrapped by graphene through electrostatic self-assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Fortunately, it has been found that the Mott-Schottky heterojunctions of metal and semiconductor can generate an oriented and stronger built-in electric field, and meantime significantly boost the transfer kinetics of electrons and ions. On the other hand, it is reported that the V 4+ in metallic VS 2 possesses a smaller radius and a higher polarity compared with Mo 4+ in MoS 2 , which is more conductive to anchoring the polysulfides in Li-sulfur batteries with favorable reversibility [20][21][22][23][24]. Nevertheless, only micro-/submicro-sized VS 2 aggregations have been reported in the literature mainly due to their thermodynamic and kinetic instability at small scale [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, it has been found that the Mott-Schottky heterojunctions of metal and semiconductor can generate an oriented and stronger built-in electric field, and meantime significantly boost the transfer kinetics of electrons and ions. On the other hand, it is reported that the V 4+ in metallic VS 2 possesses a smaller radius and a higher polarity compared with Mo 4+ in MoS 2 , which is more conductive to anchoring the polysulfides in Li-sulfur batteries with favorable reversibility [20][21][22][23][24]. Nevertheless, only micro-/submicro-sized VS 2 aggregations have been reported in the literature mainly due to their thermodynamic and kinetic instability at small scale [25][26][27].…”
Section: Introductionmentioning
confidence: 99%